Idealism and Realism Within the Ludwig Wittgenstein Philosophy. Cerbone, D. R. (2023). Wittgenstein on Realism and Idealism. Cambridge: Cambridge University Press. - Kotliarova, Anna-Mariia (Sententiae, 2025)
Review of Cerbone, D. R. (2023). Wittgenstein on Realism and Idealism. Cambridge: Cambridge University Press.